Assessing Beneficiaries’ Healthcare Satisfaction under National Health Insurance in Dar es Salaam Region, Tanzania - Yohana Andeshi Kiyoya (Indonesian Association for Public Administration, 2019)
This research is based on an empirical study of NHIF beneficiaries on the quality of healthcare received under the scheme. It investigates the extent of healthcare satisfaction as perceived by principal beneficiaries on various factors influencing healthcare, and examined challenges facing the scheme as per beneficiaries’ opinion. This research used survey method for data collection. The analysis is done using primary data from the questionnaire, which were distributed to 152 NHIF beneficiaries (employee) at the National Identification Authority (NIDA) in October 2018. Data collection instrument included a Google-based questionnaire with closed questions. Data were analyzed quantitatively using descriptive statistics (Quantitative descriptive study design). The study found unsatisfactory results on some of the services given by the scheme such as a number of dependents covered, the range of diseases covered, time for treatment intervention, time to wait for diagnostic tests, an appointment with the specialists, and time to retrieve files. It also examined budget constraints, public awareness, and acceptance of the scheme, corruption, and embezzlement as the challenge facing the scheme.